Analysis of Land Cover Change and Community Perceptions of Ecological, Social, and Economic Impact in Muara Gembong, Bekasi Regency, West Java” - Alexander Sanjaya; Faisal M Jasin; Azar Rachdian (Journal of Innovative and Creativity, 2025)
Land cover change in coastal areas is a critical environmental issue that affects the ecological, social, and economic dimensions of local communities. The study purpose was to analyse the dynamics of land cover change and to examine community perceptions of its ecological, social, and economic impacts in Muara Gembong Sub-district, Bekasi Regency, West Java. Materials and methods. This study applied a mixed-methods approach, integrating Sentinel-2A satellite imagery analysis (2015–2025) with a perception survey of 100 purposively sampled respondents. Statistical analysis involved descriptive statistics and linear regression, while spatial data were analyzed using land cover classification, accuracy assessment, and spatial overlay. Results. The results indicate a significant conversion of mangrove forests and fishponds into settlements and open land. The community perceived these changes as having negative impacts on the coastal ecosystem (biodiversity loss and coastal abrasion), as well as on social aspects (reduced access to natural resources) and economic aspects (declining income of fishermen and fish farmers). However, some respondents also recognized new economic opportunities arising from land-use conversion. The integration of spatial analysis and community perceptions revealed a strong correlation between the locations of land cover change and the levels of socio-ecological-economic vulnerability of the community. Conclusions. Land cover change in Muara Gembong (2015-2025) was mainly driven by coastal abrasion, climate change, and human activities such as population growth and infrastructure development. These changes coused ecological degradation, social conflicts, and reduced community income. Nevertheless, local communities emphasized that ecological sustainability is essential for coastal resilience and recognized new opportunities through mangrove-based ecotourism an product diversification.